The Project And Research Activity Of The Modern Teenagers: Problems And Involvement - Gulzira Abdullaeva, Manshuk Kurmanbekova,; Menlibekova, Gulbakhyt; Nurlanova, Vinara; Orazbayeva, Kuldarkhan (Opción, 2019)
The article aims to investigate the relevance of the involvement of modern teenagers in project and research activity. The research is conducted by means of the complex of theoretical and practical methods: the analysis of sources on the studied problem, comparison and generalization, empirical - observation, polling method (questioning). In result, carrying out the project, teenagers experience the most various emotions and comprehend various stages and actions, directed to obtaining of the concrete result. In conclusion, cooperation as the leading form of project and research activity contributes to the creation of favorable psychological climate in group and school, in general.